2018
DOI: 10.1136/archdischild-2017-314010
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using touch screen technology for early cognitive assessment in children

Abstract: Children as young as 24 months can complete items requiring cognitive engagement on a touch screen device, with no verbal instruction and minimal child-administrator interaction. This paves the way for using touch screen technology for language and administrator independent developmental assessment in toddlers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…Technology-based assessments as a part of AfL practices in kindergarten and preschool needs further research and development. Observations that children as young as 2-3 years can use a tablet to provide a valid assessment of cognitive skills (Twomey et al, 2018) and early literacy skills (Neumann and Neumann, 2018;Neumann et al, 2019) supports this work. Moreover, the development of ways to support the bottomup capability of teachers to collect AfL and AoL data using digital technology in the classroom is critical.…”
Section: Future Considerations For Technology-based Educational Assessupporting
confidence: 63%
See 1 more Smart Citation
“…Technology-based assessments as a part of AfL practices in kindergarten and preschool needs further research and development. Observations that children as young as 2-3 years can use a tablet to provide a valid assessment of cognitive skills (Twomey et al, 2018) and early literacy skills (Neumann and Neumann, 2018;Neumann et al, 2019) supports this work. Moreover, the development of ways to support the bottomup capability of teachers to collect AfL and AoL data using digital technology in the classroom is critical.…”
Section: Future Considerations For Technology-based Educational Assessupporting
confidence: 63%
“…Assessing toddlers using touch screen technology is the new frontier. Twomey et al (2018) found that children as young as 2-years-old can complete a cognitive assessment using a touch screen device. A range of touch screen technologies are already being developed and applied in classroom assessment as the preferred response action.…”
Section: Developmental Appropriatenessmentioning
confidence: 99%
“…Once verbal instruction is possible (usually around 2-2.5 years of age), children can be asked to inhibit actions, maintain and manipulate information in WM, and switch between different tasks (e.g., Garon, Smith, & Bryson, 2014;Mulder, Hoofs, Verhagen, van der Veen, & Leseman, 2014;Zelazo, Frye, & Rapus, 1996). The use of touchscreen devices also allows for a less verbally mediated assessment of toddlers' EF abilities (Holmboe, Fearon, Csibra, Tucker, & Johnson, 2008;Rothbart, Ellis, Rueda, & Posner, 2003;Twomey et al, 2018).…”
Section: A Wealth Of Knowledge Already Exists On the Development Ofmentioning
confidence: 99%
“…However, a growing body of data on executive function in typical development, early brain injury and a number of neurodevelopmental conditions (eg, attention-deficit hyperactivity disorder, autism spectrum disorder) provide insights into maturational factors as well as the role of experience. Assessment remains challenging and in this context Twomey and colleagues propose to use touch screen technology to evaluate early cognitive functioning with instruments that do not rely on verbal language 1. This has potentially high relevance for very young children with limited language development, like the participants in this study.…”
mentioning
confidence: 99%
“…Moreover, training of non-executive skills associated with such experience may also bias the results when measuring executive function in research or clinical practice. Many available measures, including those studied here1 implicate both executive and non-executive functions, for example, visuomotor skills. More specific motor skills required for touch screen interaction include isolation of fingers, radial selectivity of the wrist with respect to ulnar stability, precision in finger placement and control of movement timing and pressure 3.…”
mentioning
confidence: 99%